The corticosteroid prednisolone increases amygdala and insula reactivity to food approach signals in healthy young men. (January 2019) - Serfling, Georg; Buades-Rotger, Macià; Harbeck, Birgit; Krämer, Ulrike M.; Brabant, Georg
Highlights: We examined how the synthetic glucocorticoid prednisolone impacts brain areas linked with hedonic eating and motor control. The synthetic glucocorticoid prednisolone increased amygdala and insula reactivity to approach-associated food pictures. Prednisolone-induced insula reactivity to food approach pictures was associated with greater subsequent caloric intake. Prednisolone increased overall commission error rate and postcentral gyrus activity durng response inhibition. Abstract: Short- and long-term treatment with glucocorticoids is widely used in clinical practice and frequently induces features of iatrogenic Cushing syndrome, such as abdominally centered weight gain. Despite decades of glucocorticoids usage, the mechanisms underlying these side effects are still only partly understood. One possibility is that glucocorticoids impact subcortical (hypothalamus, amygdala, insula) and cortical (orbitofrontal and cingulate cortex) brain regions involved in appetite regulation and reward processing. In the present study, we used functional magnetic resonance imaging (fMRI) to study the acute effects of a prednisolone infusion on reactivity of brain reward systems to food stimuli. Twenty healthy normal-weight men were tested in a randomized, double-blind, cross-over study. After an overnight fast and infusion of either 250 mg prednisolone or placebo (always administered between 8 and 9 A M), fMRI scans were taken while presenting food and object pictures in a Go/NoGo (GNG) task. At home, participants were asked to register what they had eaten. On the following morning they came back to the lab and had a supervised ad libitum breakfast at a standardized buffet. Food-Go in contrast to Object-Go pictures yielded increased blood oxygen level dependent (BOLD) activity in hippocampus, amygdala, orbitofrontal cortex, insula and anterior cingulate cortex. Prednisolone increased activation in the bilateral amygdala and right insula for approach-associated food pictures. The buffet test did not reveal significant differences in calorie consumption or preferences of different macronutrients. However, prednisolone-induced insula reactivity to Food-Go images was associated with greater caloric intake, both at home and in the standardized buffet. In sum, we observed a specific effect of prednisolone on the BOLD response of the amygdala and insula to approach-associated food stimuli. As these brain areas have previously been implicated in hedonic eating, the present pattern of results may reflect an increased anticipated reward value of food modulated by glucocorticoids. These effects might potentially drive increased food intake and weight gain under prolonged glucocorticoid treatment.